Inhibitor of bromodomain and extraterminal domain proteins decreases transcription of Cd33 in the brain of mice subjected to systemic inflammation; a promising strategy for neuroprotection - Czapski, Grzegorz A.; Matuszewska, Marta; Cieślik, Magdalena; Strosznajder, Joanna B. (Folia Neuropathologica, 2024)
The neuroinflammation is a crucial component of virtually all neurodegenerative disorders, including Alzheimer’s disease (AD). The bacterial lipopolysaccharide (LPS), a potent activator of the innate immune system, was suggested to influence or even trigger the neuropathological alterations in AD. LPS-induced neuroinflammation involves changes in transcription of several genes, thus controlling these molecular processes may be a potentially efficient strategy to attenuate the progression of AD. Since genome-wide association studies showed that the majority of AD-related genetic risk factors (AD-GRF) are connected to the immune system, our aim was to identify AD-GRF affected in the hippocampus by LPS-induced systemic inflammatory response (SIR). Moreover, we analysed the role of bromodomain and extraterminal domain (BET) proteins, the readers of the acetylation code, in controlling the transcription of selected AD-GRF in the brain during neuroinflammation. In our study, we used a mouse model of LPS-induced SIR and mouse microglial BV2 cells. JQ1 was used as an inhibitor of BET proteins. The level of mRNA was analysed using microarrays and qPCR. Our data demonstrated that among the established AD-GRF, only the expression of Cd33 was significantly upregulated in the hippocampus during SIR. In parallel, we observed an increase in the expression of Brd4, a BET family member. JQ1 prevented an LPS-evoked increase in Cd33 expression in the hippocampus of mice. Moreover, JQ1 reduced Cd33 expression in BV2 microglial cells stimulated with blood serum from LPS-treated mice. Our study suggests that LPS-evoked SIR may increase Cd33 gene expression in the brain, and inhibition of BET proteins through suppression of Cd33 expression could be a promising strategy in prevention or in slowing down the progression of neuroinflammation and may potentially affect the pathomechanism of AD.